Consumers’ Preference towards the Usage of Organic and Non Organic Food Products - G. , Thamaraiselvi; S. , Rani; M. , Ramkumar; S. , Samundeeswari; D. , Pradeepa (International Journal of Psychosocial Rehabilitation, 2020)
Organic food products are foods that are processed without using synthetic materials such as pesticides, antibiotics, and chemical fertilizers. These are organic fruits, vegetables, dairy products, organic rice, pulses, oil, beauty products, and even readymade eatables that are processed by environmentally friendly methods. During the production, non-organic food products use synthetics. Generally, these synthetics include pesticides and fertilizers. The producers can also make a change to non-organic food products at a molecular or genetic level. This paper determined the consumers’ preference by comparing organic and non-organic food products. The conclusion was made on the basis of findings. Nowadays, many consumers prefer organic food products compared with non-organic, and usage has also increased to an extent that helps to provide an unpolluted environment. Apart from health, environment, and food, some other characteristics like taste, freshness, nutrition, and appearance also influence the consumers to prefer organic food products.